Concentraciones De Hierro En Caña De Azúcar (Saccharum Officinarum L.) Cultivada En Solución Nutritiva - Santos-Cavalcante, Valeria [UNESP]; De Mello-Prado, Renato [UNESP]; de Lima-Vasconcelos, Ricardo [UNESP]; Silva-Campos, Cid N. [UNESP] (My University, 2016)
Doubts remain about the adequate iron (Fe) concentration in nutrient solutions used for optimal plant growth, especially in gramineae like sugar cane (Saccharum officinarum L.). Therefore, the aim of this study was to evaluate the effect of Fe concentrations on growth, green color index and dry matter (DM) production in sugar cane cultivated in a nutrient solution. The hypothesis was that the nutrient solution must contain higher Fe concentration, which is used by the plant for optimum development. The study was conducted in a greenhouse with the variety IAC SP 93 3046, cultivated in pots (7.5 L) with aerated nutrient solution. The experimental design was completely randomized with five replicates and four treatments (0; 184; 368 and 551.4 μmol L-1 of Fe-EDDHA). For data analysis we used ANOVA with an F test (p≤0.05). Variables evaluated were plant height, stem diameter, leaf area, green color index, DM production, total Fe accumulation and we also performed visual diagnosis. Both leaves and roots had greater Fe accumulation of 0.28 g and 2 g per pot, respectively, on the Fe-EDDHA concentration of 184 μmol L-1. Green color index and nutrient accumulation were greater with increased Fe-EDDHA concentrations. The concentration of 184 μmol L-1 met the needs of the plant, providing a 12.2 mm diameter, 25 cm height, 750 cm2 leaf area and 4.10 g of DM per pot, 2.18 g of roots per pot and 6.28 g of whole plant per pot. The use of Fe-EDDHA chelate increased both the element's build-up in plants and green color index; and 184 μmol L-1 Fe was the adequate concentration to supply the plant's needs, promoting satisfying DM production.
Iron Concentrations in Sugar Cane (Saccharum Officinarum L.) Cultivated in Nutrient Solution
Keywords: Dry matter; Fe-EDDHA; Ferric deficiency; Green color index